Pembangunan Karakter Tangguh Bagi Para Pemuda Karang Taruna Desa Kunir Purworejo - Karyatun, Subur; Muhani, Muhani; Aisyah, Haydee Noor; Sabillah, Hanum San; Kusumaningrum, Anisa Putri; Dewi, Dyah Handayani (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2024)
Many Karang Taruna youth in Kunir Purworedjo village are of productive age but do not continue their education or work (have not yet found work or opened up employment opportunities such as entrepreneurship). Of course, this will be a problem for the country if there is a lot of unemployment. The productive age who should have high productivity are just unemployed. Therefore, this service seeks to inspire these young people to be motivated to open a business or look for work. Even if you haven’t found a job, you are motivated to carry out productive activities and can start a business. So, we need personal provisions that are tough, motivated, active and don’t give up easily. This service takes the theme of character development, which is aimed at forming strong characters for the youth of Karang Taruna, to be able to see the value of the positive side of the world, by continuing to strive to be productive. During the activity, the youth of Kunir Purworejo village showed enthusiasm. The seminar, which was held as a provision and training to become strong individuals, resulted in increased enthusiasm, knowledge and confidence for the youth of Karang Taruna. They are increasingly aware of their contribution and role for themselves, their families, the surrounding environment and also the nation. These results were obtained from interviews before and after the training.